KAJIAN PENGARUH KEBISINGAN PROYEK KONSTRUKSI TERHADAP KENYAMANAN WARGA PERMUKIMAN SEKITAR - Atma Noor Fitria; Wahyuni Susilowati; Jonathan Saputra (Jurnal Poli-Teknologi, 2022)
In the construction development process, activities such as clashes between work tools, formwork work, casting, and the use of heavy equipment have the potential to cause noise to the area around the project. This study examines the noise impact of Project X which is located close to a residential area. Noise is defined as sound that arises and is not desired but can interfere with health and comfort in the environment. This study aims to examine the effect of noise on the comfort of residents of surrounding settlements. The data were obtained by observation method, measurement with sound level meter, and questionnaire. This research refers to the Decree of the Governor of DKI Jakarta No. 551 of 2001, while the measurement method is adjusted to the Decree of the Minister of the Environment No. 48 of 1996. The results showed that most of the noise measurements exceeded the noise quality standard up to 68.45 dB(A). Simple regression analysis gives the regression equation Y = 30.811 – 0.445X, meaning that project noise has a negative effect on the comfort of residents. Hypothesis testing supports the results of simple linear regression by concluding that project noise has a significant negative effect on the comfort of residents.